The Effectiveness of Cognitive-Behavioral Play Therapy on the Aggression and Anxiety of Mentally Retarded Students - Mehrafza, Mehrnaz; Nakhostin Goldoost, Asghar; Kiamarsi, Azar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present article was done with the aim to investigate the effectiveness of cognitive-behavioral play therapy on the aggression and anxiety of mentally retarded students. Methods: The research method was quasi-experimental method with a pretest, posttest and delay post design plus control group. The statistical society of the study consisted of mentally retarded male students of second grade of elementary exceptional schools during 2021-2022 and among them 30 students were selected as the sample case and categorized in experimental group (15 students) and control group (15 students). Data collection tools included Shahim (2007) aggression questionnaire and March et al (1997) anxiety questionnaire. The validity of research instruments was confirmed by the approval of specialists, for the research instruments`, the reliability was estimated and approved by calculating Cronbach alpha coefficient (α> 0.7). Prior to the study, Pre-test of aggression and anxiety was implemented in both groups. The experimental group received cognitive-behavioral play therapy through the training package in 12 sessions, but the control group did not receive any training therapy. After the training course in the post-test stage, both of the groups answered to the same questionnaire of pre-test stage; and two months later, research instruments were performed again between both groups. Results: The research data was analyzed with between- within mixed subjects Covariance Analysis. The results revealed that the cognitive-behavioral play therapy had a positive effect on the reduction of students` aggression and anxiety and this effectiveness has been remained stable after two months(P<0.05). Conclusion: According to cognitive-behavioral play therapy effectiveness and its stability in the present research, it was suggested to apply periodically the methods of cognitive-behavioral play therapy with the aim to decrease mentally retarded students` aggression and anxiety.